2017
DOI: 10.5535/arm.2017.41.6.944
|View full text |Cite
|
Sign up to set email alerts
|

Decrement of Serum Vitamin D Level After Stroke

Abstract: ObjectiveTo investigate the serum vitamin D level and its determinant factors in stroke patients.MethodsFifty-one stroke patients who had documented serum level of 25-hydroxyvitamin D(25(OH)D) were included. Patients were divided into subacute (n=23) and chronic groups (n=28). The mean levels of 25(OH)D of the two groups were compared. Correlations between each 25(OH)D level and post-stroke duration were also analyzed. To assess other possible influencing factors, patients were subdivided by ambulation ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
5
8
1
Order By: Relevance
“…In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D . Our study was in line with the former studies from different races including in Nepal, India, Iran and Italy [14,[30][31][32][33][34][35][36]. [37].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D . Our study was in line with the former studies from different races including in Nepal, India, Iran and Italy [14,[30][31][32][33][34][35][36]. [37].…”
Section: Discussionsupporting
confidence: 91%
“…However, the above studies had a limited representation of individuals from China. In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D. Our study was in line with the former studies from different races including in Nepal, India, Iran and Italy [15,[31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%
“…This correlation among Vitamin D levels and MRS score and ambulatory status of patients were signicant. These ndings were in concordance with previous 7,8 studies. Aleri et al conducted a prospective observational study on168 acute ischemic stroke patients to evaluate the association of vitamin D levels with acute ischemic stroke and its short-term outcome.…”
Section: Figure 1 -Scatter Diagram Showing Correlation Between Duratisupporting
confidence: 93%